(untitled) (Security Dialogues, 2024)
Global security and migration are closely related to each other and mutually influence the situation in the world. Migration can be both a cause and a consequence of threats to global security. One of the main reasons for migration is instability and conflict in countries, which can lead to security threats both within and outside the country. Armed conflicts, terrorism, human rights violations, deteriorating economic situation and environmental disasters can force people to leave their homes and seek a better life in other countries. On the other hand, mass migration can cause tension in receiving countries, which can lead to social and economic problems, as well as security threats. Illegal and uncontrolled migration can contribute to crime, human trafficking and in some cases terrorist attacks. From an economic perspective, migration may potentially lead to significant negative effects such as increased unemployment among natives, increased shadow economy and may put upward pressure on housing costs. To ensure global security, it is necessary to develop a comprehensive approach to migration management that will consider the interests of all parties. This includes strengthening international cooperation, tackling the root causes of migration and ensuring sustainable development in source countries. Thus, the connection between global security and migration highlights the need for joint efforts by countries and international organizations to address the complex challenges posed by these phenomena.